What Image is Conveyed by the Webpages of Hungarian Higher Education Institutions? - Kiss, Marietta; Kun, András István (International Journal of Engineering and Management Sciences, 2018)
This exploratory study analyses the online higher education marketing practice in Hungary. It examines the homepages of all of the state accredited higher education institutions in Hungary. The selected dimensions of the examination are to measure different aspects of openness expressed by the image published on the homepages to their audience. State vs. non-state financed (and as a sub-category of the latter: church financed) institutions are compared along these dimensions, as well as universities vs. colleges (according to their status both before 2000 and present). The main finding of the research is that there is a statistically significant evidence that the homepages expressed different images for the analysed institution groups. Differentiating signals between state financed institutions vs. non-state financed institutions, as well as between universities vs. colleges were identified: the number of pictures published on the main page, the presence of sliders, the accessibility of the website to people with visual impairment and to non-Hungarian speakers, and the access to social media. State institutions and universities were found to publish a more open image via their homepages than the non-state financed institutions and the colleges.